OPTIMALISASI MODEL PROBLEM-BASED LEARNING (PBL) BERBASIS KONTEKSTUAL UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA - Aprilia, Nurkintan; Wahyuni, Endang Tri; Listyowati, Lilis (Litbang PWM Jawa Tengah, 2024)
The application of the contextual Problem-Based Learning (PBL) model is considered to enhance students' conceptual understanding of redox reactions and voltaic cells. In the context of the 21st century, which demands critical thinking, collaboration, and creativity, a learning approach that connects theory with real-life situations is crucial for developing these skills. This study aims to optimize the effectiveness of the contextual-based PBL model in enhancing students' conceptual understanding. The method used is reflective classroom action research (CAR), with two cycles based on the stages of Kemmis and McTaggart, utilizing assessment results and learning observations. The research results show a significant improvement in students' conceptual understanding. The average student score increased from 59.03 in the pre-cycle to 81.14 in cycle 1, and 88.81 in cycle 2. In addition, the percentage of student mastery also increased, from 41.67% in the pre-cycle to 66.67% in cycle 1, and reached 83.33% in cycle 2. This improvement demonstrates the effectiveness of implementing the contextual-based PBL model in enhancing students' conceptual understanding, particularly on complex materials such as redox reactions and voltaic cells.